Vulvar lichen sclerosus in women of reproductive age. Issue 3 (4th May 2021) - Kolitz, Elysha; Gammon, Laura; Mauskar, Melissa
Abstract: Vulvar lichen sclerosus (vLS) is an inflammatory skin condition that predominantly affects the vulvar and perianal regions. Approximately 50% of cases present prior to menopause; however, there is a paucity of data on vLS in women of reproductive age as well as during their pregnancies. A retrospective review was performed at two tertiary referral centers to better describe cases of vLS in women of reproductive age. Thirty-three patients with a mean age of 40 years met inclusion criteria. In this group, vulvar pruritus was the most common presenting symptom (52%); 61% had biopsy-proven vLS, 42% had at least one autoimmune condition, 21% had comorbid depression or anxiety, 33% were given an incorrect diagnosis prior to vLS, and 42% had documented nonadherence to topical steroids. Among the eight patients who became pregnant, four had cesarean deliveries and 63% were symptomatic during pregnancy. When treating a woman who presents with vulvar pruritus or skin changes, vLS should be considered.